Youth and Food Systems Transformation - Glover, Dominic; Sumberg, James (Frontiers in Sustainable Food Systems, 2020)
What, if anything, is special about youth with respect to engagement in food systems? This question is important, owing to the size of the current demographic cohort of youth, globally but especially in the majority world, as well as the large stake, and strong influence, that today’s youth will have in the development trajectories and future sustainability of food systems. Although youth is often framed as an age category for policy and bureaucratic purposes, this simplification obscures important dimensions of what being a youth means and entails. It makes comparisons and generalizations simple but misleading, because age-based classifications are nationally and culturally specific. In this paper, we argue that youth is better understood relationally, as a transitional phase within the life course. While every human being depends on consuming food, their individual transition from childhood to adulthood involves – as a very stylized generalization – a significant enlargement of autonomy and independence, as well as an increased likelihood of being substantially and directly involved in the production, distribution, procurement and/or preparation of food, as well as its consumption. However, each person’s youth transition and their relationship with food systems is uniquely shaped by specific intersections with multiple factors including gender, class, wealth, health, location, intergenerational relationships, and many others. We conclude that there are only a few, important but not necessarily dominant, ways in which youth as a group have special stakes in food systems. We elaborate on this complex picture and identify some principles to guide development research and policy that seeks to engage with youth in relation to the sustainable transformation of food systems.